Factual Consistency Trade-offs in 7B vs 3.8B Models with RAG Retrieval - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: How does reducing parameter count from 7B to 3.8B affect factual consistency scores on the HaluEval benchmark when using identical RAG retrieval contexts. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.5/10. This report is a machine-generated literature synthesis a
Machine-generated literature synthesis.